Aplikasi Irene Donut: Penerimaan dan Perubahan Sikap Orang Tua dalam Mencegah Karies Gigi Murid TK di Kota Serang - Antinah Latif; Tri Krianto; Ririn Arminingsih (Jurnal Kesehatan Gigi, 2020)
Irene donut is an application for assessing carries risk and changing the parent’s behavior. Irene donut application has rapidly grew from manul to android. The purpose of this study was to describe the user acceptance rate of Irene Donut application and to analyze the effect of “Irene Donut”  android version on parent’s attitude to prevent dental caries in children. The design of this study was pre-experimental  with repeated measure. Pre-post intervention study was conducted in Serang City, Banten-Indonesia and involved 62 parents from 4 preschools. A self-administered measurement was applied to asses user acceptance and oral health attitude before and after the program with conducted for 3 weeks. The data were analyzed using Wilcoxon test. Results showed that a statistically significance difference. That there was an effect in attitude (p=0,001). The positive attitude increased by 5,6%. Generally, User acceptance of  application  has been increased in 3 weeks (4,9%). Positive acceptance are usefulness; compatibility; triability; observability; and behavioral intention. Conclusion, Irene donut application was effective in improving oral health attitude for parents to prevent dental caries children and irene donut application has positive acceptance by the users.